Examining the behavioral intention to participate in a Cash Waqf-Financial Cooperative-Musharakah Mutanaqisah home financing model - Md Zabri, Mohd Zaidi; Mohammed, Mustafa Omar (Emerald Group Publishing Ltd., 2018)
Purpose – The purpose of this paper is to investigate the Malaysian homeowners’ intention to participate in the Cash Waqf-Financial Cooperative-Musharakah Mutanaqisah (CWFCMM) home financing model using rigorous scale validation procedures. Design/methodology/approach – An adapted questionnaire with 26 items was administered to 382 academic and supporting staffs, postgraduate and undergraduate students in three states in Malaysia. The data were analyzed using exploratory factor analysis and confirmatory factor analysis with SPSS 21 and AMOS 21, respectively. Findings – The results further support the parsimonious nature theory of planned behavior (TPB) with its three original construct of attitude, subjective norm, and perceived behavioral control and an additional construct of perceived cost advantages of the CWFCMM Model. A validated TPB scale with 24 items measured can be proposed to be used as an evaluative tool to assess the level to which the homeowners are interested to participate in the CWFCMM Model. Research limitations/implications – The modified TPB scale would also facilitate the identifications of factors that influence homeowners’ intention to opt for Islamic home financing (IHF) by non-bank Islamic financial institutions such as financial cooperative. Practical implications – The CWFCMM Model aims to harness the potential synergy between third-sector economy players such as waqf and financial cooperatives in offering affordable IHF solution to potential homeowners. Social implications – The CWFCMM Model may enable the Malaysian homeowners to enjoy a more affordable IHF solution, thereby, among others, reducing the purchase and monthly repayment affordability of Malaysians. Originality/value – There is a dearth of Islamic financial services selection studies, especially within the non-banking, Islamic financial services milieu. The CWFCMM Model, which has been developed by the authors, enriches the limited literature on this subject matter. It will also add value to understand how the customers would react to an alternative IHF provider